An Acoustic Analysis of the English Plosive Sounds (/p/ and /b/) Pronounced by Students in the Department of English at Sirte University (Sirte University Journal of Humanities, 2025)
This study aims to investigate whether Libyan Arabic (LA) learners are able to distinguish between the English plosive sounds (/p/ vs. /b/). In addition, it aims to find out whether the learners’ first language (L1) interferes with their production of the target sounds. Data were collected from five LA learners, enrolled in the Department of English, Sirte University. The students produced five English minimal pairs, containing the English stops /p/ and /b/, and five LA words with the Libyan Arabic stop consonant /b/ in an initial position. The participants were also asked to record the same words embedded in fixed carrier phrases in both English and Libyan Arabic.  The voice onset time (VOT) values of English stops /p/ and /b/, and the LA consonant sound /b/ were measured using Praat software. In total, there were 300 tokens targeted for analysis. The findings showed that the participants were able to distinguish between /p/ and /b/ in their productions. This provides evidence against the general assumption that Arab learners have difficulty with English voiceless sound /p/.  However, the results obtained from this study showed that some participants had difficulties with the pronunciation of the English voiced sound /b/, which they produced with positive values (i.e. values similar to those of its voiceless counterpart /p/). In addition, the statistical analysis of the data revealed no significant effect of the students’ L1 on their production of the target sounds. The results obtained from the current study are expected to provide valuable recommendations for EFL teachers and material writers.
Keywords: Instrumental Analysis; English Stops; VOT; Pronunciation; Libyan Arabic Learners